Kontribusi Biaya Lingkungan, Green Accounting, CSR, dan Ukuran Perusahaan dalam Meningkatkan Profitabilitas Perusahaan - Kartika Wulandhari; Nera Marinda Machdar (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study aims to analyze the relationship between environmental costs, green accounting, and corporate social responsibility (CSR) on corporate profitability, with company size as a moderating factor. The findings reveal that environmental costs can have both positive and negative impacts on profitability, depending on how these costs are managed. Green accounting has been shown to enhance operational efficiency and transparency, positively affecting profitability. Additionally, CSR offers long-term benefits for corporate image and customer loyalty, though its effects may not always be immediately apparent. Company size moderates these relationships, with larger companies having greater advantages in managing environmental and social aspects compared to smaller companies. This study highlights the importance of strategic management of environmental costs, implementation of green accounting, and execution of CSR to support corporate sustainability and profitability.